Competitive profile of business process outsourcing companies in Bogotá: principal component analysis (2016)
The aim of this research based article is to analyze the competitive profile of Bogota BPOs, by assessing them with the Model of Indicators for Sustainable Management and Associativity (MIGSA in Spanish) and by using the Principal Component Analysis (PCA) to distribute the variables studied in a small number of groups, in order to account for aspects that illustrate the variability in the companies management. Thanks to this study two axes were defined: the first one relates to sustainable aspects that are internal to the companies while the second one sets elements of external sustainability. Both of them generate four different competitiveness profiles which allow organizations to generate strategic planning as well as establish their location, to improve their position on the market.